The Effect of Work Life Balance and Work Engagement on Employee Loyalty and Performance - Rahmansyah, Ahmad Maulana; Utami, Hamidah Nayati; Prasetya, Arik (Profit: Jurnal Adminsitrasi Bisnis, 2023)
The purpose of the research is to determine the effect of work-life balance and work-engagement on employee loyalty and performance at a coffeeshop in Malang city. Competition between cafe entrepreneurs is getting tougher, so the growth of coffeeshops is also getting faster, and employees are always required to develop their performance and increase productivity and loyalty at work which leads to the Coffeeshop's performance. Coffeeshop's performance must pay attention to the work-life balance and work-engagement of employees as an important factor to make a policy to maintain work productivity and employee performance. This study uses quantitative research methods and the research sample was 54 employees selected by random sampling technique. The data collection was a questionnaire technique, and be analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS). The result of the research is that worklife-balance and work-engagement are one of the factors that influence employee performance and  loyalty in working at a coffeeshop in Malang city.